Design and development broadband monopole antenna for in-door application - Ali Abdulateef Abdulbari; Z. Zakaria; Sharul Kamal Abdul Rahim; Yaqthan Mahmood Hussein; Mustafa Mohammed Jawad; Ayad Muslim Hamzah (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2020)
This paper describes the broadband monopole antenna refers to a signal wideband of the frequencies, which can be divided the signal into channels of the frequency bins.  Aim this paper to design and development broadband monopole antenna. The monopole antenna was designed by adding slot to the radiated patch antenna with a single feed line, which reduced the size and the design complexity. A rectangular patch antenna was presented using feed line to decrease the ground plane with a suitable gap distance. The broadband monopole antenna was designed with a frequency range of 800 MHz–3 GHz, with Bandwidth 0.66(dB), reflection coefficients and return loss. The frequency-dependent characteristic impedance was included. It can be used in various broadband applications in used commercially for various communication systems such as 4G (LTE), WiMAX and WLAN (LTE), remote sensing, biomedical, and mobile wireless. Apart from that, this technology is environment-friendly; an antenna which consists of reception and transmission. The antenna is simulated by using computer simulation (CST) software; a low cost of 4.4 permittivity FR-4 substrate is used. The measurement result is accepted with simulation result, proving the acceptable broadband operation for this proposed structure.